'Hemos ido a redimir al redentor': The Old 'Paleto' As Mentor in Miguel Delibes' El disputado voto del Señor Cayo (1978). Issue 4 (21st April 2022) - Giménez-Rico, Isabel Durán
Abstract : El disputado voto del Señor Cayo (1978), a novel by Miguel Delibes, is constructed around a road trip, in which a candidate for a political party in the 1977 Spanish elections and two militants travel to a remote Castilian village in order to gain Mr Cayo's vote. In this article I provide a reading of the candidate's journey into 'deep Spain' as an example of the 'Hero's Journey' monomyth, and focus on the character of the old 'paleto', a naturally 'wise old man' whom the politicians try to 'redeem', only to find that they are the ones to be redeemed.